2017
DOI: 10.1002/jbt.21922
|View full text |Cite
|
Sign up to set email alerts
|

Asiaticoside hinders the invasive growth of keloid fibroblasts through inhibition of the GDF‐9/MAPK/Smad pathway

Abstract: Higher expression of growth differentiation factor-9 (GDF-9) in keloids compared with hypertrophic scars and normal skin tissues has been reported recently. The present study was performed to investigate the role of GDF-9 in keloid pathogenesis, and to elucidate its implication for asiaticoside in the keloid management. The data showed that GDF-9 could enhance the proliferation, migration, and invasion of keloid fibroblasts (KFs), while it only slightly elevated collagen expression, indicating that the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Of note, NOTCH signaling, mitogenactivated protein kinase signaling, and Toll-like receptor pathways were found to be altered in keloid-prone individuals after wounding with a decrease in pathway activity. These pathways have already been suggested to play a role in keloid disease, and our analysis provides further evidence to support their involvement (Bagabir et al, 2011;Syed and Bayat, 2012;Wu et al, 2017). Moreover, DNA repair and p53 signaling pathways were also highlighted (Yamauchi et al, 2018).…”
Section: To the Editorsupporting
confidence: 76%
See 1 more Smart Citation
“…Of note, NOTCH signaling, mitogenactivated protein kinase signaling, and Toll-like receptor pathways were found to be altered in keloid-prone individuals after wounding with a decrease in pathway activity. These pathways have already been suggested to play a role in keloid disease, and our analysis provides further evidence to support their involvement (Bagabir et al, 2011;Syed and Bayat, 2012;Wu et al, 2017). Moreover, DNA repair and p53 signaling pathways were also highlighted (Yamauchi et al, 2018).…”
Section: To the Editorsupporting
confidence: 76%
“…This analysis identified the mitogen-activated protein kinase signaling pathway as the only gene set to be significantly dysregulated in the keloid prone subjects 6 weeks after wounding (see Supplementary Tables S4, S5 online). Notably, other published data have shown that inhibition of mitogenactivated protein kinase hinders invasive growth of keloid fibroblasts (Wu et al, 2017).…”
Section: To the Editormentioning
confidence: 99%
“…All the above results confirmed that asiaticoside can inhibit MMT via TGF-β/Smad signaling. Earlier studies have revealed the anti-MMT effect of asiaticoside in keloid fibroblasts and lung epithelial cells [14]. However, there have been no reports in the context of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Asiaticoside (shown in Fig.1) is the main component of triterpenoid saponins extracted from Centella asiatica with a clear formula. Emerging evidence has indicated that asiaticoside shows antioxidant, antiinflammatory, anti-fibrotic and other pharmacological effects [14][15][16]. In the PD field, the protective effects of asiaticoside against MMT and PD-related ROS remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Other possibilities are onion extract and asiaticoside (a triterpenoid from a herb called Centella asiatica), which have already been used widely to treat keloids. [91][92][93] Another possibility is trace elements such as copper and zinc, which are known to play essential roles in wound healing 94 and/or fibrosis. 95 However, Bang and Dashti did not find any evidence that changes in these elements (eg, zinc, copper, manganese, and selenium) contribute to cutaneous pathological scarring.…”
Section: Other Dietary Ingredientsmentioning
confidence: 99%